2004
DOI: 10.1002/cjce.5450820109
|View full text |Cite
|
Sign up to set email alerts
|

Voidage Profiles in a Slot‐Rectangular Spouted Bed

Abstract: Local voidages were determined using optical fibre probes for 1.4 and 2.4 mm glass beads in slot‐rectangular spouted beds of width 150 mm. The effects of air inlet flow rate, slot width and bed thickness were investigated. Spout widths were determined from standard deviations of local voidage fluctuations. Both spout and annulus voidages increased with increasing air flow. Annulus voidages were usually higher than corresponding loose‐packed voidages and decreased with increasing height. Annulus and spout voida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…They applied this technique to measurements in a high‐density circulating fluidized‐bed riser. Others in our laboratory (e.g., Freitas et al,17 Wang,18 and Chen19) have successfully deployed optical fiber probes in a variety of systems. Therefore, optical fiber probes were used in the present work.…”
Section: Methodsmentioning
confidence: 99%
“…They applied this technique to measurements in a high‐density circulating fluidized‐bed riser. Others in our laboratory (e.g., Freitas et al,17 Wang,18 and Chen19) have successfully deployed optical fiber probes in a variety of systems. Therefore, optical fiber probes were used in the present work.…”
Section: Methodsmentioning
confidence: 99%
“…Passos et al [15] thickness-to-width ratio, which should be considered in the scale-up process. Freitas et al [19] indicated similarity between slot-rectangular and conventional spouted beds in voidage profiles…”
Section: -Introductionmentioning
confidence: 95%
“…Freitas et al identified different flow regimes in a slot‐rectangular spouted bed based on pressure fluctuations. Freitas et al studied related profiles of voidage in a SRSB by means of an optical fibre probe. Both spout and annulus voidages increased with increasing air flow, and the spouts became nearly circular as the static bed height increased, despite the rectangular column and slot geometry.…”
Section: Introductionmentioning
confidence: 99%